Seroprevalence of chicken infectious anemia virus infection among some poultry species in Maiduguri, Nigeria (Journal of Advanced Veterinary and Animal Research, 2018)
Objective: This study was designed to investigate the seroprevalence of Chicken Infectious Anemia Virus (CIAV) among selected poultry species in Maiduguri, Nigeria.Materials and method: ELISA kit (X-Ovo FlockscreenTM, Cat. No.V085 5 plates. February, 2014 - Xnew kit format), Chicken serum, enzyme conjugate reagent, adhesive cover, wash buffer, substrate reagent, stop solution. Serum samples from village chickens, broilers, layers, ducks, turkeys and geese in Maiduguri were tested for CIAV antibodies using Enzyme Linked Immunosorbent Assay (ELISA) as per the manufacturer’s protocols at the Viral Research Laboratory, Faculty of Veterinary Medicine, University of Maiduguri, Nigeria. The results were presented in simple percentages, bar charts and analyzed using SPSS Version 16 software.Results: Out of 944 sera from different species of poultry tested, an overall seroprevalence of 38.5% (n=363/944) was recorded in this study. The species distribution showed village chickens had 41.4% (n=166/944) prevalence, layers with 23.0% (n=12/52), broilers 46.6% (n=146/313), turkeys 23.6% (n=30/127), ducks 13.7% (n=4/29) and geese 22.7% (n=5/22) prevalence for CIAV antibodies.Conclusion: The result of this study shows that CIAV infection is present among different poultry species in the study area and therefore highlight the need for continuous surveillance so as to control further spread of the virus.http://doi.org/10.5455/javar.2017.d232